Experimental study on the dynamic filtration control performance of N2/liquid CO2 foam in porous media. (15th August 2017) - Lv, Qichao; Li, Zhaomin; Li, Binfei; Zhang, Chao; Shi, Dashan; Zheng, Chao; Zhou, Tongke
Highlights: N2 /liquid CO2 foam showed an outstanding filtration control performance. Leak coefficient was decreased by the increasing of foam quality (<80%). Low quality foam (∼30%) controlled filtration effectively under high pressure drop. The damage of N2 /liquid CO2 foam to porous media could be eliminated with time. Abstract: Liquid CO2 has been successfully used as a fracturing fluid and injected into rock formations to enhance oil and gas production. However, the difficulty in controlling the filtration of liquid CO2 in porous media limits its application. The goal of this study is to investigate the dynamic filtration control performance of N2 /liquid CO2 foam with a fluorochemical (HFE) as stabilizer. A laboratory apparatus has been specially designed and built for the generation of N2 /liquid CO2 foams and the measurement of their viscosity and filtration rate under high pressure (10–25 MPa). The test results show that after liquid CO2 and HFE were mixed with N2, the N2 /liquid CO2 foams were generated and showed significant viscosity improvement compared to liquid CO2 . The foams exhibited better filtration control performance compared to liquid CO2 and liquid CO2  + N2 systems. Although the addition of HFE did not result in the formation of filter cake, the foam showed a wall-building behavior, which could be explained by the CO2 phase change in porous media. As foam quality increased from 28% to 92%, the leakoff coefficient and spurt loss volume first decreased until the foam became unstable and changed into mist flow. The leakoff coefficient of foam increased with the increase in permeability of porous media. For foam with the quality of about 50–80%, a change of 2 orders of magnitude in permeability resulted in a change of 1 order of magnitude in leakoff coefficient. At high pressure difference, lower initial quality foam (∼30%) showed better filtration performance than higher initial quality foam (∼80%). When the pressure difference was high enough to cause the CO2 phase change from liquid to gas in the porous media, the initial foam damage after filtration became obvious, but the damage could be eliminated with time by gas return flow. Thus, by using N2 /liquid CO2 foam in porous media, the fluid filtration behavior could be controlled without damage.